Hybrid Cryptographic Approach for Internet Ofhybrid Cryptographic Approach for Internet Of things Applications: A Review - Mohamed, Nur Nabila; Mohd Yussoff, Yusnani; Saleh, Mohammed Ahmed; Hashim, Habibah (Universiti Utara Malaysia Press, 2020)
Cryptography is described as the study of encrypting or secret Cryptography is described as the study of encrypting or secret writing of data using logical and mathematical principles to protect information. This technique has grown in importance in computing technologies for banking services, medical systems, transportation and other Internet of Things (IoT)-based applications which have been subjected to increasing security concerns. In cryptography, each scheme is built with its own respective strength, but the implementation of single cryptographic scheme into the system has some disadvantages. For instance, symmetric encryption method provides a cost effective technique of securing data without compromising security. However, sharing the secret key is a vital problem. On the other hand the asymmetric scheme solves the secret key distribution issue; yet the standalone technique is slow and consumes more computer resources compared to the symmetric encryption. In contrast, hashing function generates a unique and fixed-length signature for a message to provide data integrity but the method is only a one-way function which is infeasible to invert. As an alternative to solve the security weakness of every single scheme, integration of several cryptographic of every single scheme, integration of several cryptographic schemes which are also called the hybridization technique is being proposed offering the efficiency of securing data and solving the issue of key distribution. Herein, a review study of articles related to hybrid cryptographic approach from 2013to 2018 is presented. Current IoT domains that implemented hybrid approaches were identified and the review was conducted according to the category of the domain. The significant findings from this literature review included the exploration of various IoT domains that implemented hybrid cryptographic techniques for improving performance in related works. From the findings, it can be concluded that the hybrid cryptographic approach has been implemented in many IoT cloud computing services. In addition, AES and ECC have been found to be the most popular methods used in the hybrid approach due to its computing speed and security resistance among other schemes.